Comparison of the clinical outcomes of connective tissue and acellular dermal matrix in combination with double papillary flap for root coverage: A 6-month trial - Gholam Ali Gholami; Arezoo Saberi; Mahdi Kadkhodazadeh; Reza Amid; Daryoosh Karami (Wolters Kluwer Medknow Publications, 2013)
Background: Different techniques have been proposed for the treatment of gingival recession. The majority of current procedures use autogenous soft-tissue grafts, which are associated with morbidity at the donor sites. Acellular dermal matrix (ADM) Alloderm is an alternative donor material presented to reduce related morbidity and provide more volume of the donor tissue. This study aimed to evaluate the effectiveness of an ADM allograft for root coverage and to compare it with a connective tissue graft (CTG), when used with a double papillary flap. Materials and Methods: Sixteen patients with bilateral class I or II gingival recessions were selected. A total of 32 recessions were treated and randomly assigned into the test and contralateral recessions into the control group. In the control group, the exposed root surfaces were treated by the placement of a CTG in combination with a double papillary flap; and in the test group, an ADM allograft was used as a substitute for palatal donor tissue. Probing depth, clinical attachment level, width of keratinized tissue (KT), recession height and width were measured before, and after 2 weeks and 6 months of surgery. Results: There were no statistically significant differences between the test and control groups in terms of recession reduction, clinical attachment gain, and reduction in probing depth. The control group had a statistically significant increased area of KT after 6 months compared to the test group. Conclusion: ADM allograft can be considered as a substitute for palatal donor tissue in root coverage procedure.